Does Education Raise Productivity and Wages Equally? The Moderating Roles of Age, Gender and Industry - François Rycx; Yves Saks; Ilan Tojerow (National Bank of Belgium, 2015)
The labour market situation of low-educated people is particularly critical in most advanced economies, especially among youngsters and women. Policies aiming to increase their employability either try to foster their productivity and/or to decrease their wage cost. Yet, the evidence on the misalignment between education-induced productivity gains and corresponding wage cost differentials is surprisingly thin, inconclusive and subject to various econometric biases. We investigate this issue using rich Belgian linked employer-employee panel data for the period 1999-2010. Moreover, we provide first evidence on the moderating roles of age, gender and industry in the relationship between education, productivity and wage costs. Controlling for simultaneity issues, time-invariant workplace characteristics and dynamics in the adjustment process of dependent variables, findings support the existence of a `wage-compression effect', i.e. a situation in which the distribution of wage costs is more compressed than the education-productivity profile. This effect, robust across industries, is found to disappear among older cohorts of workers and to be more pronounced among women than men. Overall, findings suggest that particular attention should be devoted to the productivity to wage cost ratio of low-educated workers, especially when they are young and female, but also to policies favouring gender equality in terms of remuneration and career advancement.
Keywords: C33; I21; J24; J31; 330; Education; labour costs; productivity; linked panel data